Silver‐Catalyzed Synthesis of 1‐Chloroalkynes Directly from Terminal Alkynes. Issue 9 (15th April 2015) - Shi, Dunfa; Liu, Zhiwen; Zhang, Ziyu; Shi, Wei; Chen, Hao
Abstract An efficient method to prepare 1‐chloroalkynes was investigated. The method involved the use of readily available terminal alkynes and a catalytic amount of a silver salt with N‐chlorosuccinimide as the chlorinating agent under mild conditions. Compared with the existing process, this method has a broad substrate scope: 19 examples were explored, and the products were obtained in excellent yields and were easily isolated by vacuum distillation. Moreover, recycling of the catalyst was achieved by simple filtration and desiccation, which made the method more economic and environmentally benign.